Clinical findings in determining referral criteria for coronavirus disease (COVID-19) patients at a makeshift isolation center of Bekasi, West Java - Stefi Geovani Valentin Hayon; Florentina Priscilia; Hariri - (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
COVID-19 has become a pandemic concern with the clinical manifestations ranging for asymptomatic to severe organ failure. Early contact tracing and isolation are important keys to slow the infection spread within communities. Clinical triage and early recognition of warning signs on admission are needed to classify patients based on clinical severity. Due to the limited capacity of hospital settings for COVID-19 patients, a makeshift isolation center is needed for all confirmed and suspected cases with mild or no symptoms who will be provided with basic medical care, frequent monitoring, and rapid referrals. During observations, the physician needs to raise early alertness of the patient who is at risk to develop a worse outcome. This study reports five cases of patients who came with mild or no symptoms at initial presentation and developed into worsening disease progression after several days of observation. These patients developed shortness of breath, fatigue, abdominal disturbances, and chest pain. These findings were supported by the physical examinations that showed a decrease in blood oxygen saturation. Similarly, with the Centers for Disease Control and Prevention (CDC) criteria for the early warning signs, these patients were referred to the hospital-based isolation setting that could provide more advanced and optimal management. This study describes clinical manifestations of COVID-19 patients to decide the ideal time for referral.